The Role of the PAX8/PPARγ Fusion Oncogene in Thyroid Cancer - Kimberly A. Placzkowski; Honey V. Reddi; Stefan K. G. Grebe; Norman L. Eberhardt; Bryan McIver (PPAR Research)
Thyroid cancer is uncommon and exhibits relatively low mortality rates. However, a subset of patients experience inexorable growth, metastatic spread, and mortality. Unfortunately, for these patients, there have been few significant advances in treatment during the last 50 years. While substantial advances have been made in recent years about the molecular genetic events underlying papillary thyroid cancer, the more aggressive follicular thyroid cancer remains poorly understood. The recent discovery of the PAX8/PPARγ translocation in follicular thyroid carcinoma has promoted progress in the role of PPARγ as a tumor suppressor and potential therapeutic target. The PAX8/PPARγ fusion gene appears to be an oncogene. It is most often expressed in follicular carcinomas and exerts a dominant-negative effect on wild-type PPARγ, and stimulates transcription of PAX8-responsive promoters. PPARγ agonists have shown promising results in vitro, although very few studies have been conducted to assess the clinical impact of these agents.